Does FDI really matter to economic growth in India? - Yoon Jung Choi; Jungho Baek (Economies, 2017)
The main contribution of this article is to examine the productivity spillover effects from India's inward foreign direct investment (FDI), controlling for trade, in the framework of the cointegrated vector autoregression (CVAR). For this purpose, using the Solow residual approach the aggregate total factor productivity (TFP) in India is estimated to measure FDI-induced spillovers. The results show that the inflow of FDI to India indeed improves TFP growth through positive spillover effects. We also find that trade appears to have a detrimental effect on TFP growth in India.
Keywords: C22; F14; 330; cointegrated VAR; FDI; India; total factor productivity